Implementation of Transformational Leadership in Village Institutions - Muhammad Faisal Riza; Andy Fefta Wijaya; Irfan Kharisma Putra; Ahmad Bachtiar Arif (Program Pascasarjana Universitas Negeri Makassar, 2023)
The village head has a key role in developing his village with various leadership styles in order to improve the village economy. One popular leadership style is transformational leadership. Therefore, this research aims to identify the implementation of transformational leadership in village institutions in improving the village economy. This research is descriptive research with a qualitative approach. This research was conducted using in-depth interviews with four village heads including village officials and business actors in Jombang Regency, including Ngampungan Village, Galengdowo Village, Wonomerto Village, and Carangwulung Village. This village was chosen because it has a fairly developed rural tourism in Jombang Regency. The research results show that the Head of Galengdowo Village has the highest level of application of transformational leadership among other village heads, followed by the Heads of Wonomerto and Carangwulung Villages who have similar characteristics.